2020
DOI: 10.2319/111119-712.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of orthodontic space closure using micro-osteoperforation and passive self-ligating appliances or conventional fixed appliances:

Abstract: Objectives To examine the effect of micro-osteoperforation (MOP) on the space closure rate using passive self-ligating or conventional brackets. Materials and Methods This was a two-arm parallel randomized controlled trial undertaken at the outpatient department of a dental college. There were 60 participants (30 women and 30 men) who fulfilled the inclusion criteria. Both the study and control groups were subjected to MOPs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
1
15
0
2
Order By: Relevance
“…Gómez et al, en un estudio clínico compara la fricción entre brackets autoligado pasivo y brackets convencionales en el cierre de espacios, observó que no existe diferencia significativa en la fricción al emplear los dos sistemas en el cierre de espacios pues los valores obtenidos para el autoligado (1,5mm) y para el convencional (1,41mm) (S. L. Gomez et al, 2019), lo que concuerda con el ensayo clínico realizado por Monini et al donde tampoco encuentra diferencias en la fricción entre los dos sistemas de brackets empleados durante el cierre de espacios maxilar (0,71mm autoligado y 0,72 mm convencional) y en la mandíbula (0,54 autoligado y 0,60 mm convencional) (Monini et al, 2019), Mittal et al demuestra similares resultados cuando emplea brackets de autoligado pasivo ( 0,81± 0,07 a 0,81mm± 0,12 en el maxilar y 0,78 ±0,08 a 0,77± 0,15 mm en la mandibula) con los convencionales (0,79±0,05mm a 0,80±0,12mm maxilar y 0,78±0,11mm a 0,78±0,07mm mandíbula) (Mittal et al, 2020), estos estudios estan de acuerdo con la revisión sistemática de Yang et al, en la que también no encuentra diferencias en la fricción durante el cierre de espacios entre los dos tipos de brackets (Yang et al, 2018).…”
Section: Discussionunclassified
“…Gómez et al, en un estudio clínico compara la fricción entre brackets autoligado pasivo y brackets convencionales en el cierre de espacios, observó que no existe diferencia significativa en la fricción al emplear los dos sistemas en el cierre de espacios pues los valores obtenidos para el autoligado (1,5mm) y para el convencional (1,41mm) (S. L. Gomez et al, 2019), lo que concuerda con el ensayo clínico realizado por Monini et al donde tampoco encuentra diferencias en la fricción entre los dos sistemas de brackets empleados durante el cierre de espacios maxilar (0,71mm autoligado y 0,72 mm convencional) y en la mandíbula (0,54 autoligado y 0,60 mm convencional) (Monini et al, 2019), Mittal et al demuestra similares resultados cuando emplea brackets de autoligado pasivo ( 0,81± 0,07 a 0,81mm± 0,12 en el maxilar y 0,78 ±0,08 a 0,77± 0,15 mm en la mandibula) con los convencionales (0,79±0,05mm a 0,80±0,12mm maxilar y 0,78±0,11mm a 0,78±0,07mm mandíbula) (Mittal et al, 2020), estos estudios estan de acuerdo con la revisión sistemática de Yang et al, en la que también no encuentra diferencias en la fricción durante el cierre de espacios entre los dos tipos de brackets (Yang et al, 2018).…”
Section: Discussionunclassified
“…A disposable device was explicitly designed by PROPEL Orthodontics (Ossining, NY) to deliver perforations. 3,11,37 It has a manually adjustable tool with varying lengths of 3, 5, and 7 mm for the corresponding depth of the perforation decided. 12 Postoperative care after the minor surgical procedure requires no pain medications usually.…”
Section: Micro-osteoperforations: Literature Searchmentioning
confidence: 99%
“…Despite several confounders that can alter the results associated with the administration of MOPs, such as the age of the patient, 6,37 gender of the patient, 34 short durations of study, 4,9,32,36 limited sample size, 3,35 type of tooth movement required during the treatment, occlusal interferences that can affect tooth movement rates, 11 extraction sites not properly healed which could confound by causing an inflammatory reaction other than the one induced by MOP placement, inadequate oral hygiene, periodontal problems, usage of NSAIDS, habitual usage of a specific quadrant for chewing affecting the unequal distribution of occlusal forces, 11 to mention a few. 3,29,32,33 Limitations No technique, till yet explored 12 in the literature, is without its fair share of limitations.…”
Section: Micro-osteoperforations: Literature Searchmentioning
confidence: 99%
“…6 , 7 Less invasive techniques such as piezocision, corticision, and micro-osteoperforation (MOP) without flap elevation have also been reported to be effective. 8 - 13 …”
Section: Introductionmentioning
confidence: 99%
“…6,7 Less invasive techniques such as piezocision, corticision, and microosteoperforation (MOP) without flap elevation have also been reported to be effective. [8][9][10][11][12][13] Wilcko et al 14 applied selective decortication lines and made cuts as deep as 0.5 mm around the target teeth, and Baloul et al 15 demonstrated that this surgical intervention accelerated the rate of tooth movement during the early stages of treatment. Dutra et al 16 reported that alveolar decortications resulted in enhanced bone remodeling in the region of tooth movement.…”
Section: Introductionmentioning
confidence: 99%